1979
DOI: 10.1093/nar/6.5.1843
|View full text |Cite
|
Sign up to set email alerts
|

The effects of salt concentration and H-1 depletion on the digestion of calf thymus chromatin by micrococcal nuclease

Abstract: We have removed histone H1 specifically from calf thymus nuclei by low pH treatment, and studied the digestion of such nuclei in comparison with undepleted nuclei. By a number of criteria the nuclei do not appear damaged. The DNA repeat-length in nuclear chromatin is found to be the same (192 +/- 4 bp) in the presence or absence of H1. These experiments demonstrate that the core histone complex of H2A, H2B, H3, and H4 can itself protect DNA sequences as long as 168 bp from nuclease. Our interpretation is that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 26 publications
5
40
0
Order By: Relevance
“…It has been shown that micrococcal nuclease activity is only slightly reduced in 0.3 mM Ca 2ϩ compared with 2 mM Ca 2ϩ (47), whereas the specificity of the enzyme remains the same (48). This indicates that the observed difference in micrococcal nuclease digestion pattern reflects the change in the chromatin structure rather than the activity of the micrococcal nuclease, which is supported by early studies where a similar effect was observed at various concentrations of monovalent cations (49,50). DISCUSSION …”
Section: The Alterations In Histone-dna Contacts In Isolated Core Parsupporting
confidence: 70%
“…It has been shown that micrococcal nuclease activity is only slightly reduced in 0.3 mM Ca 2ϩ compared with 2 mM Ca 2ϩ (47), whereas the specificity of the enzyme remains the same (48). This indicates that the observed difference in micrococcal nuclease digestion pattern reflects the change in the chromatin structure rather than the activity of the micrococcal nuclease, which is supported by early studies where a similar effect was observed at various concentrations of monovalent cations (49,50). DISCUSSION …”
Section: The Alterations In Histone-dna Contacts In Isolated Core Parsupporting
confidence: 70%
“…Observations consistent with salt-dependent nucleosome sliding were also made by Weischet et al (65). It was not until the 1990s that this phenomenon was characterized more thoroughly by Bradbury and coworkers, who exploited the fact that nucleosomes located at different positions had altered mobilities during native polyacrylamide gel electrophoresis (48,49).…”
mentioning
confidence: 66%
“…This particle contains Ϸ1 3 ⁄4 turns of DNA and only the four core histones and is defined as a relatively kinetically stable intermediate produced from digestion of chromatin with micrococcal nuclease. However, histone octamer-DNA complexes containing anywhere from Ϸ100 to 180 bp of DNA have been shown to be stable, and the number of superhelical wraps of DNA observed around the octamer varies from Ϸ1 to 2, depending on the conditions of observation (1,31). These products are likely to reflect a balance between tail-DNA interactions and the affinity of micrococcal nuclease for nucleosomal DNA and further suggest that the core histone tails require a complete nucleosome subunit for appropriate binding interactions.…”
Section: Discussionmentioning
confidence: 99%